Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
a) 4a + 15 = - 5
4a= -20/:4
a= -5
b) 3x + 2 = 2(x + 1)
3x+2=2x+2
x=0
c) -5x + 10 = - 2x – 8
-3x= -18/:(-3)
x= 6
d) 7x + 14 = 5x – 22
2x= -36/:2
x= -18
e) 2(x – 3) + 3(4 – x) = 5
2x-6+12-3x=5
-x+6= 5
-x= -1/*(-1)
x=1
f)x + 2(3x – 4) = 53 + 2x
x+6x-8=53+2x
7x-8=53+2x
5x=45/:5
x=9
g) 3x - 2+ 5x+ 6- x= 4x - 2+ 6x
6x+4=10x -2
-4x= -6/:(-4)
x=3/2=1 1/2
_________________________
a) -5x + 10 = -2x – 8
-3x= -18/:(-3)
x=6
b) 7x + 14 = 5x – 22
2x= -36/:2
x= -18
c) -3 + 2x – 6 = 3 – 4x
2x-9=3-4x
6x=12/:6
x=2
d) -5x + 12 + x = 2x – 12
-4x+12= -12
-4x= -24/:(-4)
x=6
e) 2(x – 3) + 3(4 – x) = 5
2x-6+12-3x=5
-x+6=5
-x= -1/*(-1)
x=1
f) 2(x + 4) – 5(x + 3) = 2
2x+8-5x-15=2
-3x-7=2
-3x= -9/:(-3)
x=3
g) 3(x – 4) – 2(2x – 5) = -4
3x-12-4x+10=4
-x-2=4
-x=6/:(-1)
x=-6
h) -2(x + 3) + 4(2x+ 3) = -6
-2x-6+8x+12= -6
6x+6 =-6
6x= -12/:6
x= -2